Backlash of policy dismantling in the production of invisibility: when pesticides cease to be a public problem - Coudel, Emilie; Santos, Beatriz Abreu dos; Silva, Danielle Wagner; Piva, Mariana; Nasuti, Stéphanie; Folhes, Ricardo Theophilo; Bonnet, Marie-Paule; Lima, Denise Valéria; Passos, Carlos José Sousa; Nakamura, Ione; et al. (Sustainability in Debate, 2023)
Brazil is one of the world’s largest consumers of pesticides, but their impacts on the population are still rarely recognised as a public problem. During the governments of Lula and Dilma, several social participation spaces were created to discuss this issue. In this article, we discuss how dismantling these spaces has contributed to producing invisibility regarding the impacts of pesticides. We were confronted with this issue when building a citizen observatory in the metropolitan region of Santarém, Pará, in partnership with family farmer unions. Based on interviews, participant observation, and focus groups, we analyse how the dismantling of pesticide regulation has occurred nationally and how it influenced the territorial level. Despite research showing the impacts of pesticides, the progressive dismantling of social participation spaces, such as the Regional Forum to Combat the Impacts of Pesticides in Santarém, has led to the invisibility of the impacts caused by their use.